Characteristics of hybrid tube with Fe-high Si alloy lining by centrifugal casting for thermochemical water-splitting iodine-sulfur process - Ikuo IOKA (The Japan Society of Mechanical Engineers, 2016)
An iodine-sulfur process based thermochemical water-splitting (IS process) for hydrogen production has been developed by JAEA as application of a high-temperature gas cooled reactor. The IS process includes a severe corrosion environment which is made to boil and decompose concentrated sulfuric acid. Two kinds of brittle materials, SiC, Si3N4 and Fe-high Si alloy, were reported as materials having enough corrosion resistance in this corrosion environment. The hybrid tube consisting of the Fe-high Si alloy with boiling sulfuric acid-resistant and the carbon steel with the ductility was produced by a centrifugal casting. An evaluation of the characteristics was carried out by hardness measurements, corrosion tests and thermal cyclic tests. The configuration of the hybrid tube by the centrifugal casting was 240 mm in outer diameter, 200 mm in inner diameter and 980 mm in length. The inner layer of the Fe-high Si alloy and the outer layer of the carbon steel stuck at the interface without pores. There is no intermetallic compound at the interface between the carbon steel and the Fe-high Si. The Fe-high Si alloy lining showed enough corrosion resistance in boiling concentrated sulfuric acid. Thermal cyclic tests (100-900 °C) were executed in order to evaluate the interface between the carbon steel and the Fe-high Si alloy. There was no detachment of the interface though the groove and the cracks were generated in the vicinity of the interface by thermal cycling. It is believed that the cracks parallel to the interface is attributed to the tensile stress during the heating process of thermal cyclic test and the flake graphite precipitate on the grain boundary. It was confirmed that the interface possessed the enough strength.